Hepatitis B incidence and prevention with antiretroviral therapy among HIV-positive individuals in Uganda. (27th March 2017) - Seremba, Emmanuel; Ssempijja, Victor; Kalibbala, Sarah; Gray, Ronald H.; Wawer, Maria J.; Nalugoda, Fred; Casper, Corey; Phipps, Warren; Ocama, Ponsiano; Serwadda, David; Thomas, David L.; Reynolds, Steven J.
Abstract : Objective: Antiretroviral therapy (ART) may interfere with replication of hepatitis B virus (HBV), raising the hypothesis that HBV infection might be prevented by ART. We investigated the incidence and risk factors associated with HBV among HIV-infected adults in Rakai, Uganda. Methods: We screened stored sera from 944 HIV-infected adults enrolled in the Rakai Community Cohort Study between September 2003 and March 2015 for evidence of HBV exposure. Serum from participants who tested anti-hepatitis B core-negative (497) at baseline were tested over 3–7 consecutive survey rounds for incident HBV. Poisson incidence methods were used to estimate incidence of HBV with 95% confidence intervals (CIs), whereas Cox proportional regression methods were used to estimate hazard ratios (HRs). Results: Thirty-nine HBV infections occurred over 3342 person-years, incidence 1.17/100 person-years. HBV incidence was significantly lower with ART use: 0.49/100 person-years with ART and 2.3/100 person-years without ART [adjusted HR (aHR) 0.25, 95% CI 0.1–0.5, P < 0.001], and with lamivudine (3TC) use: 0.58/100 person-years) with 3TC and 2.25/100 person-years without 3TC (aHR 0.32, 95% CI 0.1–0.7, P = < 0.007). No new HBV infections occurred among those on tenofovir-based ART. HBV incidence also decreased with HIV RNA suppression: 0.6/100 person-years with 400 copies/ml or less and 4.0/100 person-years with more than 400 copies/ml (aHR, 6.4, 95% CI 2.2–19.0, P < 0.001); and with age: 15–29 years versus 40–50 years (aHR 3.2, 95% CI 1.2–9.0); 30–39 years versus 40–50 years (aHR 2.1, 95% CI 0.9–5.3). Conclusion: HBV continues to be acquired in adulthood among HIV-positive Ugandans and HBV incidence is dramatically reduced with HBV-active ART. In addition to widespread vaccination, initiation of ART may prevent HBV acquisition among HIV-positive adults in sub-Saharan Africa.